2015
DOI: 10.2147/ndt.s73836
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline upregulates cyclic AMP response element binding protein and brain-derived neurotrophic factor in the hippocampus of cerebral ischemia rats and improves behavioral deficits

Abstract: Background and purposeThe cAMP response element binding protein (CREB) plays an important role in the mechanism of cognitive impairment and is also pivotal in the switch from short-term to long-term memory. Brain-derived neurotrophic factor (BDNF) seems a promising avenue in the treatment of cerebral ischemia injury since this neurotrophin could stimulate structural plasticity and repair cognitive impairment. Several findings have displayed that the dysregulation of the CREB–BDNF cascade has been involved in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 56 publications
3
12
0
1
Order By: Relevance
“…Several findings have shown that the dysregulation of the CREB-BDNF cascade has been involved in cognitive impairment [29]. The neurons of the hippocampus of aged animals showed a down-regulation of BDNF and p-CREB expression, associated with learning and memory impairment [30, 31], which was also similar with our result.…”
Section: Discussionsupporting
confidence: 91%
“…Several findings have shown that the dysregulation of the CREB-BDNF cascade has been involved in cognitive impairment [29]. The neurons of the hippocampus of aged animals showed a down-regulation of BDNF and p-CREB expression, associated with learning and memory impairment [30, 31], which was also similar with our result.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings showed a relationship between obesity-associated cognitive decline and decreases in the density of dendritic spines, primary sites of excitatory synapses, which have been linked to synaptic plasticity and cognitive function (Yuste and Bonhoeffer, 2001;Yuste, 2011). Restoring dendritic spine density in obese mice to control values with minocycline treatment was associated with restored cognitive function.…”
Section: Discussionmentioning
confidence: 54%
“…Because dendritic spines, the primary sites of excitatory synapses, have been linked to synaptic plasticity and cognition (Yuste and Bonhoeffer, 2001; Yuste, 2011), we hypothesized that they might be altered by obesity. Using DiI labeling, we examined dendritic spine density in two neuronal populations of the dorsal hippocampus: the GCs of the DG and the pyramidal cells of the CA1 region.…”
Section: Obesity Is Associated With Decreased Dendritic Spine Densitymentioning
confidence: 99%
“…Post-stroke cognitive impairment can range from mild cognitive decline to dementia [ 47 ]. Cerebral ischemia induces free radical formation, glutamate stress, oxidative stress and hypoxic stress, all of which contribute to neuronal injury and cognitive impairments [ 48 ]. Stroke-related dementia is associated with fluctuations in C-reactive protein (CRP), IL-6 and IL-10 in blood serum and cerebrospinal fluid [ 47 ].…”
Section: Stroke-induced Dementia As a Potential Target For Melatonmentioning
confidence: 99%